2016
DOI: 10.1016/j.rmb.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Seed structure and in vitro seedling development of certain Laeliinae species (Orchidaceae)

Abstract: Seeds and seedlings of neotropical Laeliinae species (Cattleya loddigesii, Cattleya tigrina, Hadrolaelia purpurata, Laelia anceps, Schomburgkia gloriosa, and Sophronitis cernua) were studied. The seed germination process and the seedling grown in vitro are described. Seeds of the studied species are unitegmic and have conspicuous thickening in the anticlinal and inner periclinal cell walls. The embryo consists of a relatively long and multicellular suspensor. At first stage of seedling development, the embryo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Most orchid species are endangered because of over collection and loss of habitat, so there is an urgent need to develop techniques to conserve them both in situ as well as ex situ [1]. Seed morphology is an important trait related to biological and ecological processes such as seed dormancy and germination [2,3], adaptation to habitat for seed dispersal [4][5][6][7], and seed storability [8]. Therefore, investigating seed morphology is relevant to understanding the plant's reproduction under natural conditions and to devise optimal protocols for seed storage and propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Most orchid species are endangered because of over collection and loss of habitat, so there is an urgent need to develop techniques to conserve them both in situ as well as ex situ [1]. Seed morphology is an important trait related to biological and ecological processes such as seed dormancy and germination [2,3], adaptation to habitat for seed dispersal [4][5][6][7], and seed storability [8]. Therefore, investigating seed morphology is relevant to understanding the plant's reproduction under natural conditions and to devise optimal protocols for seed storage and propagation.…”
Section: Introductionmentioning
confidence: 99%
“…This is in concordance with other authors, where the effectiveness of the organic components (pineapple juice and coconut water) have allowed a verification in the in vitro culture of a great variety of orchid species. (Gallo et al, 2016;Salazar et al, 2013). Nonetheless, Pedroza (2009), found that the addition of AIA (0.5 mg.L -1 ) to the MS culture medium, promoted the development phases of Epidendrum elongatum.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have achieved asimbiotic germination using different simple means with minerals, vitamins, hormones and sugars (Kauth et al, 2011;Arditti & Ghani, 2000;Knudson, 1946). Likewise, cultures have been improved supplementing the media with organic components (Gallo et al, 2016;Salazar et al, 2013;Salazar & Cancino, 2012). The present research aims to determine the most suitable culture medium for asymbiotic seed germination and in vitro propagation of C. trianae for the species conservation.…”
Section: Introductionmentioning
confidence: 99%
“…As recently reported by Caballero-Villalobos et al [16], the species is nectarless and self-compatible, although it is pollinator-dependent. Some morphological investigations on the vegetative portions of this species have been carried out by Silva Júnior et al [17] and Gallo et al [18]. The former studied leaf characteristics and chlorophyll content of this species after the applications of different urea concentrations during in vitro experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The former studied leaf characteristics and chlorophyll content of this species after the applications of different urea concentrations during in vitro experiments. Gallo et al [18] performed an anatomical investigation on seed and protocorm from six species belonging to the genus Cattleya, C. purpurata included. Anatomical investigations provide important information to assess species identity, to better understand physiological processes, or to study phylogenetic relationships between taxa [19].…”
Section: Introductionmentioning
confidence: 99%